Yazılı Basında Ve İnternet Gazeteciliğinde Kullanılan Haber Fotoğraflarının Karşılaştırılması - Uçak, Olcay (The Turkish Online Journal of Design Art and Communication, 2012)
Photograph, enter a new process in the transformation of traditional media into digital media. Thereby photograph is the most important transporter of the visual culture in the internet environment. The photograph whose area of usage continues to expand from science to industry, from communication to education become widespread more quickly by the development of technology. In media, the usage of photo offer alternative options to reporters that they can transfer meanings which they are not able to fit in the written texts. The photo’s characteristic of recording events carry a meaning of the power it has got. This power, with the high-speed the photo transfer gets in the digital environment increases its importance. In this study, news photos which are used in internet course as a means of communication and expresssion will be analyzed by the method of semiotics. By comparing the photograph analysis to be made with the photo datas used in printed media, the present stage in the environment of newspaper and internet will be discussed.
Keywords: Visual Culture; New Media; News Photo; Görsel Kültür; Yeni Medya; Haber Fotoğrafları